Mapping the global development of pawnshop research: A bibliometric analysis of scopus-indexed publications - Serah Novarida Mabel (Journal of Sustainability, Society, and Eco-Welfare, 2026)
Background: Pawnshop is a key non-bank financial service providing short-term liquidity for communities with limited access to formal banking. Along with economic uncertainty and social vulnerability, academic studies on pawnshops have developed rapidly across various disciplines. This study aims to map and analyze the global development of pawnshop research, identify major thematic structures, and examine the multidisciplinary nature of the literature. Methods: This study employs a bibliometric approach using secondary data obtained from the Scopus database covering publications from 2016 to 2025. A total of 59 relevant articles were analyzed using bibliometric techniques, including publication trend analysis, country and institutional contributions, funding sources, subject areas, and keyword co-occurrence analysis supported by network, overlay, and density visualizations. Findings: The results show that pawnshop research has grown steadily and is highly multidisciplinary, involving social sciences, economics, business, health, and policy studies. Keyword co-occurrence analysis reveals five main thematic clusters: alternative financial services and microfinance, social behavior, risk and criminality, sensitive regulation related to public safety, and sharia-based pawnshops. Furthermore, pawnshop research focuses on risk-oriented and regulatory issues toward financial inclusion, ethical finance, eco-social welfare, and socially responsive pawnshop models. These findings demonstrate a strong relationship between theoretical perspectives on financial inclusion and social vulnerability with the empirical development of pawnshop research. Conclusion: This study concludes that pawnshop is a complex socio-economic phenomenon vital for fostering community resilience, sustainability, and eco-social welfare, which must be understood through an integrated and multidisciplinary perspective. The bibliometric mapping provides a comprehensive overview of the state of the art and highlights future research directions in non-bank financial services. Novelty/Originality of this article: This article offers a comprehensive bibliometric synthesis of global pawnshop research by integrating thematic structures, research dynamics, and multidisciplinary perspectives, providing a holistic understanding that has not been systematically explored in previous studies.